Responding to globalised food‐borne disease: risk assessment as post‐normal science - Waltner‐Toews, David (EFSA J, 2019)
Since the 1960s, global trade in food and feed has increased rapidly, and the number of countries at least partially reliant on this trade has sprouted into complex International Agrifood Trade Networks (IATN). IATNs have obscured the already‐labyrinthine causal webs of food‐borne diseases, and the usual methods for demonstrating causal links between IATNs and food‐borne diseases yield results that are, at best, inconclusive. At the same time, responses are being offered which will, if implemented, likely to have unintended negative consequences. In this context, risk analysis (RA) is being used in situations for which it was not designed, in which facts are uncertain, values are in dispute and assessments are embedded in contested power arrangements, with heterogeneous consequences for diverse stakeholders around the world. To characterise and manage the most serious unintended food‐borne disease consequences of globalisation, the most effective way forward will require reframing of RA as a post‐normal science.